Simultaneous fault detection and antisaturated control based on dynamic observer for inverted pendulum control system. (5th April 2019) - Pang, Guochen; Cao, Jinde; Chen, Xiangyong; Qiu, Jianlong
Summary: This paper focuses on the problem of simultaneous fault detection and antisaturated control for an inverted pendulum control system. The system input is the acting control voltage that generates the force on the cart. However, the acting control voltage is obviously limited by the voltage amplitude. This means that the actuator of the constructed system model is saturated. Hence, the detector/controller unit produces two signals: the detection and antisaturated control. In this process, the effects of disturbances and noises on detection and control purposes need to be suppressed. Finally, two simulation examples verify the effectiveness of the method.